The Effect of a Mindfulness-Based Stress Reduction Program on Premenstrual Symptoms: A Randomized Controlled Trial - Cetin, Nurdilan Sener; Kirca, Ayca Solt (Wiley, 2023)
IntroductionPremenstrual syndrome (PMS) is an important health problem that affects women of childbearing age. Mindfulness, a meditation practice that cultivates the acceptance of events as they occur in the moment without judgment, is a promising strategy to help women cope with PMS. This study aimed to test the efficacy of a mindfulness-based stress reduction (MBSR) program in decreasing premenstrual symptoms compared with a control group. MethodsThis study was a prospective, single-masked randomized controlled trial conducted between February and April 2022 with 90 university students. Participants were women between 20 and 30 years of age, scored at least 45 on the Premenstrual Syndrome Scale (PMSS), and were not receiving other treatments for PMS. Participants were randomized into experimental (MBSR) and control groups in a 1:1 allocation. MBSR was provided in 8 weekly sessions lasting 2.5 hours and a 6-hour silence retreat during week 6. Symptoms of PMS were evaluated with the PMSS at baseline and postintervention. Differences between groups were compared postintervention using analysis of covariance to correct for baseline scores. The study was registered at before the data collection process was initiated (NCT05191108). ResultsOf the 90 enrolled participants, 74 participants completed the study and postintervention assessment (37 in each group). Immediately postintervention, the women in the experimental group had significantly lower PMS symptoms than women in the control group (PMSS total score, 96.35 vs 123.02; P < .001). The effect size for the change in premenstrual symptoms was large (partial eta(2), 0.510). Specific symptoms measured by the PMSS subscales all showed significant reductions in scores in the MBSR group compared with the control group. DiscussionA mindfulness stress reduction program was effective in reducing premenstrual symptoms. MBSR programs may be used as a therapy for PMS. Future studies should test MBSR in larger and more diverse groups of women with PMS.
Keywords: midwife; mindfulness stress reduction program; nurse; premenstrual syndrome